A critical analysis of NGOs in addressing HIV and AIDS in the context of gendered inequality: The case of Makhanda, Eastern Cape, South Africa - Mhavika, Moreblessing (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
South Africa has the highest number of people living with HIV and AIDS in the world. The HIV pandemic has, and continues to have, negative implications for communities and individuals, especially women, in South Africa and beyond. HIV and AIDS has left women disproportionately more infected and affected than men because of social, cultural and economic factors, leading to the feminisation of HIV. South African NGOs have tried to fill in the gap and to respond to the HIV pandemic, either independently or in partnership with government departments. In this context, the purpose of this thesis is to provide a critical analysis of NGO programmes in Makhanda (in the Eastern Cape Province) to ascertain whether NGOs address the feminisation of HIV and, if so, how. In doing so, the study utilises qualitative analysis with the use of interviews, a focus group discussion and primary documents as research methods. The study concludes that local government in Makhanda has failed to address women's vulnerabilities to HIV and that it does not provide a sufficiently enabling environment for NGOs in this regard. In addition, inadequate funding from donors, alongside issues of accountability and the failure to engage in HIV programmes from a perspective founded in feminism, were factors found to contribute to NGOs not fully considering women's vulnerabilities to HIV. Resultantly, NGOs in Makhanda rarely, at least intentionally, address the feminisation of HIV.
Keywords: AIDS (Disease) -- Sex factors; AIDS (Disease) -- Social aspects -- South Africa -- Makhanda; HIV infections -- Sex factors; HIV infections -- Social aspects -- South Africa -- Makhanda; HIV-positive women -- South Africa -- Makhanda; Non-governmental organizations -- South Africa -- Makhanda